Factors Determining Culinary Tourism Visits: A Systematic Literature Review - Hasibuan, Anggy Qurnia Ra’afi; Wardi, Yunia; Rino, Rino (Universitas Proklamasi 45, 2025)
This article conducts a Systematic Literature Review (SLR) to identify key factors determining visit and revisit intentions in culinary tourism. Guided by PRISMA 2020, Scopus is used to select Q1 journal articles (2020–2025) that examine culinary/gastronomy tourism, ambidextrous leadership (AL), entrepreneurial orientation (EO), digital promotion, and virtual reality/virtual tours (VR/VT). Ten eligible studies are synthesized into three clusters: (1) AL and EO as internal strategic capabilities, (2) VR/VT and digital promotion as experiential and technological drivers, and (3) culinary experiences and local wisdom as core cultural assets. The review presents a comprehensive framework incorporating managerial capabilities and digital experiences.